Surface analysis of early retrieved polyethylene tibial inserts for both knees in total knee replacement. (January 2020) - Tan, M.Y.; Liza, S.; Khadijah, S.M.P; Abbas, A.A.; Merican, A.M.; Ayob, K.A.; Zulkifli, N.W.M.; Masjuki, H.H.
Highlights: By analysing the surface of an early retrieved implants, both inserts (6 and 8 months) exhibited numerous scratch marks oriented in various directions and pits. Abrasive wear and oxidation induced wear were found as the main wear damage modes of an early-retrieved UHMWPE tibial inserts which undergoes revision surgery within 1 years of their index arthroplasty. Our data demonstrated a strong association between the change of molecular weight and degradation mechanical properties with oxidation and surface wear damage mode for both inserts. Abstract: This study involves the failure analysis of a pair of ultra-high-molecular-weight-polyethylene (UHMWPE) knee tibial inserts from Scorpio® fixed-bearing total knee system by Stryker, which were retrieved from Total Knee Replacements (TKR) that was performed on 64 years old male patient with periprosthetic joint infection detected on both knees. Although the implants were removed due to infection, surface analysis was essential to be studied in order to analyse the surface damage mode of short-term implants. This study reports relevant damage mechanisms seen in early-retrieved UHMWPE tibial inserts (implanted for 6 and 8 months) and further analysis of chemical, physical and mechanical properties that possibly accompanied with failure. The surface characterization was done using a 3D laser microscope and Scanning Electron Microscope (SEM) to evaluate surface damage and dimensional change of both UHMWPE tibial inserts. Nano-indentation is used to measure the hardness and elasticity modulus of the tibial inserts. Attenuated Total Reflection-Fourier Transform Infra-Red (ATR-FTIR), Differential Scanning Calorimetry (DSC) and Gel Permeation Chromatography (GPC) were used to characterize the chemical and physical properties of the inserts. In present study, retrieved polyethylene inserts with short implantation duration was considered to have high-grade wear modes. The high incidence of micro pits (with the average depth of 27.5 μm for 6 months insert and 18 μm for 8 months insert) and scratches as the observed surface defects strengthen the role played by the particles upon defects generation for both tibial inserts. The average surface roughness of 6 and 8 months inserts were 1.6798 μm and 1.2376 μm, respectively. The rough surface (4.207 μm) of region 4 at the lateral compartment proves that the 6 months tibial insert suffered more damage due to loosening defect where the radiolucencies (the gap between bone and cement) were seen below medial and lateral aspects of the tibial tray. Our data demonstrated a strong association between the change of molecular weight and degradation of mechanical properties with wear for both inserts. The oxidation induced wear mechanism was observed on 6 months old insert due to the presence of delamination features with the evidence of in vivo oxidation from IR analysis.